Avaliação do potencial antifúngico e antivirulência do cinamaldeído contra isolados clínicos de onicomicose e obtenção de bioproduto com atividade antifúngica tópica - MENDES , Iven Neylla Farias Vale (2021)
Introduction: Onychomycosis represents great therapeutic challenges both due to the reduced quantity of available drugs and the resistance to the substances available in the clinic. With this, it is necessary to search for alternative therapies and an important source are essential oils, including cinnamon essential oil, whose main compound is cinnamaldehyde (CNMA), which has several known biological activities. The aim of the present study was to evaluate the antimicrobial potential in vitro, including a nail infection model, and in vivo CNMA, as well as the anti-virulence properties in order to obtain a topical formulation based on the compound. Material and Methods: The antimicrobial activity of CNMA was evaluated in vitro against clinical isolates of Candida and filamentous fungi obtained from skin lesions of patients with AIDS, by obtaining the Minimum Inhibitory Concentration (MIC) and the Minimum Fungicidal Concentration (MFC). The combinatory antimicrobial effect between CNMA and the itraconazole (ITL) and terbinafine (TRB) antifungals was also assessed using the chessboard test. The anti-adherence and anti-biofilm effects of CNMA were determined by counting the number of Colony Forming Units (CFU) / ml and the toxicity test was performed on larvae of Tenebrio molitor. Nails were collected from healthy volunteers and used in a filamentous fungal infection model (104 conidia / mL). The infected nails were then treated with CNMA or TRB and incubated for 30 days at 27 ° C. After incubation, the nails were evaluated in a stereomicroscope with a 75 × magnification. The effect of CNMA on infection of T. molitor larvae with Candida (106 cells / mL) was verified after treatment with different concentrations of the compound (MIC, MIC × 2 or MIC × 4) and compared to the infected and control larvae treated with antifungals (Fluconazole and ITL). Data were analyzed by the statistical program GraphPad Prism 5 (2007). The evaluation of CNMA fungal potential (microdilution) was made by the chi-square independence test ( 2) or by Fisher's exact test. Biofilm tests were evaluated by ANOVA test. The Kaplan-Meier method was used to calculate the survival percentages and the Log-Rank test to compare survival curves. A value of p < 0.05 was considered statistically significant. Results: CNMA showed an antifungal effect with MICs between 19.5 and 156 µg / mL, reduced adherence and interfered with Candida biofilm formation (p <0.0001). CNMA also interacted synergistically with terbinafine and itraconazole, significantly reducing the growth of fungi (FIC = 0.1645 for C. parapsilosis and 0.26 ≥ FIC ≥ 0.01 for Trichophyton interdigitale). In the toxicity test, the lowest survival rate was 84.2% at a concentration of 156 µg / mL, suggesting that in the tested concentrations, CNMA has low toxicity. The compound reduced the development of fungi in infection already established in fragments of nails more quickly compared to conventional tested antifungals. Cinnamaldehyde reduced fungal mycelium in nails infected with T. interdigitale, Trichophyton rubrum and Microsporum gypseum. Synergistic concentrations between cinnamaldehyde and itraconazole and terbinafine were also observed in T. interdigitale Larvae infected with Candida and treated with CNMA had a longer survival than those treated with itraconazole, which corroborates the therapeutic potential of the compound. A topical formulation for nails based on vegetable oil containing CNMA (concentrations according to the results obtained) was developed for further testing. Conclusion: CNMA showed antifungal and anti-virulence properties against yeasts and filamentous fungi in concentrations below 156 µg / mL, and a synergistic effect with the antifungal agents itraconazole and terbinafine making it possible to be used in therapy in combination with traditional drugs. The fungal populations of yeasts and filamentous fungi infecting T. molitor larvae and nail fragments were reduced after treatment with CNMA. Thus, CNMA proved to be a substance that did not present toxicity in the tested therapeutic concentrations and proved to be an alternative for the treatment of cutaneous fungal diseases. In addition, cinnamaldehyde appears as an antimicrobial substance with therapeutic potential alone or in combination with other compounds.